Kekuatan Tanda Tangan Elektronik dalam Konsep Cyber Notary Menurut Presfektif Permen Kominfo Nomor 11 Tahun 2022 (International Forum of Researchers and Lecturers, 2025)
A signature is a signature that represents a symbol as a result of a statement or a statement, a product whose development has been very rapid, and has become increasingly popular, an information technology and electronics company which is increasingly popular. With that, the Ellektronilk transaction was born and the use of ElleKtronilk's signature process as an aspect human error. So from iltul pelrlul pelnyelsulailan dulnila dilgiltal telrkailt konselp cybelr notary in ellelktronilk transactions. Ilnil research examines the effectiveness of ellelktronilk's signature in the notary cybelr concept meldnulrult prelsfelktilf pelrmeln komilnfo number 11 of 2022 and implements the research meltodel yulrildils normilvel yailtul sulatul development towards hulkulm problems from the perspective of the US implementation of legal regulations that are valid, article 15 paragraph (3) UlUlJN which regulates that notaries There are also other laxities that are regulated in the regulation of regulations. One of them is the ability to sell transactional financial assets carried out through e-Notary (el-Notary) which ultimately results in deeds of ilkrar, waqf and airplane mortgages. Telrbult legal regulations can be taken from UlUl ILTEl as a legal stand to support the implementation of el-Notary in carrying out electronic transactions. The ability to complete an Otelnilk deed as well as to sign it personally as a legal agreement between Common Law and Civil Law Notaries, between Cybelr Notary and Ellelktronilk Notary. The three things that have been developed have resulted in a formalized renewal strategy produced in a complete, reliable, reliable and safe system through a collaborative strategy developed by several companies or companies using the company's technology team. telmul, selkalilguls' harmony and practice in carrying out the position of notary in Ilndonelsila. The resulting conclusion is that Ellektronilk's signature strength in the notary cybelr concept in the Pelrmeln Komilnfo prelsfelktilf number 11 of 2022, still has no strong legal strength.